Influence of Cross-Linking Agent Concentration/Beta Radiation Surface Modification on the Micro-Mechanical Properties of Polyamide 6 - Martin Ovsik (MDPI AG, 2021)
This study focuses on the problematic of polyamide 6 containing various concentrations of cross-linking agent that was exposed to electron radiation. It is important to improve the material properties of polymers as much as possible. This endeavor can be realized by numerous methods, one of which is radiation exposure. This study investigates the effect of electron beam radiation in doses ranging from 66 to 132 kGy on the micro-mechanical properties of polymers, specifically polyamide 6 filled with 1, 3 and 5 wt.% of cross-linking agent triallyl isocyanurate (TAIC). The changes in the material brought by the radiation exposure were quantified by measurements of indentation hardness and modulus, which were the main measured micro-mechanical properties. Furthermore, thermo-mechanical analysis (TMA) was chosen to confirm the results of the material cross-linking, while the effect of degradation was investigated by Fourier-transform infrared spectroscopy (FTIR). In pursuit of complete evaluation, the topography of the test subject’s surface was explored by atomic force microscopy (AFM). The optimal concentration/radiation ratio was found in polyamide 6 enriched by 5 wt.% concentration of TAIC, which was irradiated by 132 kGy. Material treated in such a way had its indentation hardness by 33% and indentation modulus improved by 26% in comparison with the untreated material. These results were subsequently confirmed by the TMA and FTIR methods.